Thyroid Function and Anti-thyroid Antibodies in Pediatric Anti-NMDAR Encephalitis - Chen, Lianfeng; Wu, Wenlin; Tian, Yang; Zeng, Yiru; Hou, Chi; Zhu, Haixia; Zheng, Kelu; Zhang, Yani; Gao, Yuanyuan; Peng, Bingwei; Yang, Sida; Wang, Xiuying; et al. (Frontiers in Neurology, 2021)
Objective: Recent studies found that changes of thyroid antibodies (ATAbs), thyroid hormone, and non-thyroidal illness syndrome (NTIS) characterized by thyroid hormone inactivation with low triiodothyronine and high reverse triiodothyronine followed by suppressed thyroid-stimulating hormone (TSH) in adult anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis were associated with disease severity. This study aimed to explore thyroid function and ATAbs in pediatric anti-NMDAR encephalitis and their clinical association. Methods: We retrospectively analyzed the clinical data of 51 pediatric cases with anti-NMDAR encephalitis hospitalized in Guangzhou Women and Children's Medical Center from August 2016 to 2019. Results: A percentage of 52.9% of patients belonged to the ATAb (+) group, with 26 cases both positive for anti-thyroid peroxidase antibodies (TPOAb) and anti-thyroglobulin antibodies (TGAb), and one patient only positive for TPOAb. A percentage of 62.7% of patients had at least one abnormality in terms of FT3, free thyroxin (FT4), or TSH levels. Meanwhile, 45.1% of patients were diagnosed with NTIS. Among 25 cases retested for thyroid function 2 months after the initial test, the respectively decreased FT3 and FT4 in 13 and 11 cases on admission returned to normal or closer normal than before; TPOAb in eight cases and TGAb in 12 cases were changed from positivity to negativity. Compared with onset, the level of TPOAb and TGAb at relapse remained stable or significantly decreased, respectively. Compared with the ATAb (–) group, the ATAb (+) group had an older onset age, a higher ratio of movement disorders, elevated rate of sleep disorders, increased anti-nuclear antibody positivity rate, and higher ratio of more than one course of intravenous immunoglobulin treatment. There were no significant differences between the NTIS and non-NTIS groups in clinical characteristics. Conclusion: Anti-thyroid antibody positivity, abnormality of FT3, FT4, or TSH levels and NTIS are frequent in pediatric anti-NMDAR encephalitis. Thyroid antibody and thyroid hormone abnormalities could be improved through the course of treatment of anti-NMDAR encephalitis. Cases with ATAbs (+) are at older onset ages and more likely to be treated by intravenous immunoglobulin therapy more than once. Unlike adult anti-NMDAR encephalitis, NTIS might not be associated with the clinical characteristics of anti-NMDAR encephalitis in pediatric patients.